Analysis Of Needs For Development Of Basketball Curriculum Age Group 9-12 Years - Tria Muhamad Aris; Ali Mu’arifuddin (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2020)
The method used in this research is quantitative descriptive. The instrument used for data collection used a questionnaire with research subjects; basketball coaches, basketball players, basketball referees and sports teachers in East Java. The results of this study showed 54% stated that there was a basketball curriculum for the 9-12 year age group issued by the Indonesian Basketball Association (PERBASI) while the remaining 46% stated that there was no curriculum issued by Perbasi. While the most surprising result was that 92% of the subjects could not show evidence of a basketball curriculum. Based on these data, it can be concluded that the existence of a basketball curriculum is still a big question mark, so it is necessary to develop a basketball curriculum that can become literature for coaches, players or sports practitioners in Indonesia.